Kinematic Structure of the Stellar Population of the Solar Neighborhood by Gaia DR3 - Postnikova, E. S.; Vereshchagin, S. V.; Chupina, N. V.; Mosunova, D. A.
The data of modern catalogs allow us to consider in detail the issue of the spatial velocity distribution. The stars in the solar vicinity make it possible to avoid errors and draw detailed conclusions about their kinematics. For a corrected study, we took a sample of stars from the Gaia DR3 within 300 pc. This area contains a number of star clusters and streams. It was found that in the circumscribed vicinity the direction of the stars is divided into several vast concentrations, the apex of motion of which lies in the direction of the motion of the Sun and in the direction of motion of the Ursa Major group, which in turn is divided into two separate groups in direction in space. In addition, a group of stars is considered, which, according to their kinematic characteristics, most likely belong to a halo or bulge. High-velocity stars are also considered under the assumption of their nature.
Keywords: Astrometry; Space Sciences; Archaeoastronomy and Astronomy in Culture